Impact of the Chemokine Receptors CXCR4 and CXCR7 on Clinical Outcome in Adrenocortical Carcinoma - Chifu, Irina; Heinze, Britta; Fuss, Carmina T.; Lang, Katharina; Kroiss, Matthias; Kircher, Stefan; Ronchi, Cristina L.; Altieri, Barbara; Schirbel, Andreas; Fassnacht, Martin; Hahner, Stefanie (Frontiers in Endocrinology, 2020)
Chemokine receptors have a negative impact on tumor progression in several human cancers and have therefore been of interest for molecular imaging and targeted therapy. However, their clinical and prognostic significance in adrenocortical carcinoma (ACC) is unknown. The aim of this study was to evaluate the chemokine receptor profile in ACC and to analyse its association with clinicopathological characteristics and clinical outcome. A chemokine receptor profile was initially evaluated by quantitative PCR in 4 normal adrenals, 18 ACC samples and human ACC cell line NCI-H295. High expression of CXCR4 and CXCR7 in both healthy and malignant adrenal tissue and ACC cells was confirmed. In the next step, we analyzed the expression and cellular localization of CXCR4 and CXCR7 in ACC by immunohistochemistry in 187 and 84 samples, respectively. These results were correlated with clinicopathological parameters and survival outcome. We detected strong membrane expression of CXCR4 and CXCR7 in 50% of ACC samples. Strong cytoplasmic CXCR4 staining was more frequent among samples derived from metastases compared to primaries (p=0.01) and local recurrences (p=0.04). CXCR4 membrane staining positively correlated with proliferation index Ki67 (r=0.17, p=0.028). CXCR7 membrane staining negatively correlated with Ki67 (r=-0.254, p=0.03) but positively with tumor size (r=0.3, p=0.02). No differences in progression-free or overall survival were observed between patients with strong and weak staining intensities for CXCR4 or CXCR7. Taken together, high expression of CXCR4 and CXCR7 in both local tumors and metastases suggests that some ACC patients might benefit from CXCR4/CXCR7-targeted therapy.